Barriers to Encourage Motivation in Relation to Work Performance of Nurses in Buleleng District Hospital - Budiastri; Ayu Indrayathi; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Nurses at hospitals regularly receives criticism from the general public, negatively commenting on their lack of patient care, lack of professionalism and diminished quality of service. Survey findings on patient satisifaction at Buleleng Public Hospital from 2011 indicate that 2.03% of patients remained unsatisfied with staff workplace attitudes and 6.39% felt that nursing service overall was unsatisifactory. Preliminary interviews with ward nurses on 24 November 2012 exposed a number of issues: a lack of career support and development for nurses, including opportunities to expand their skills, and a lack of workplace satisifaction from patient supplementary income. Weakness regarding technical support and motivation from ward supervisors evidently also has an impact on nurses workplace motivation and therefore quality of service. This research investigates the influence of supervision, career development, supplementary income support, and administrational records on the workplace attitude of nursing staff. Methods: Research was formulated using qualitative and phenomenology methods. Informants were purposively selected. Data was collected through in-depth interviews and administration documentation study and analysed using thematic analysis. Results and conclusion: Findings indicated that little monitoring and evaluation of nurse workplace attitudes, a lack of support and motivational direction from supervisors, administrational documentation issues, minimun supplementary income support, as well as career development had a large impact on nurse quality of care. Most dominant variables included supervision, career development and supplementary income support.